1981
DOI: 10.1063/1.440841
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet laser photolysis: Primary photochemistry of Fe(CO)5 in PF3

Abstract: Articles you may be interested inTime-resolved infrared diode laser spectroscopy of the ν1 band of the iron carbonyl radical (FeCO) produced by the ultraviolet photolysis of Fe(CO)5We have studied the photolysis of mixtures of Fe(CO), and PF J with a KrF laser operating at 248 nm. The product yields of Fe(COh(PFJh. Fe(CO),(PFJh. and Fe(CO).PF J have been measured as a function of laser fluence and mixture composition. A simple kinetic model appears to explain semiquantitatively the observed dependence of produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The available experimental observations show that upon COphotolysis of the pentacarbonyl metal complex M(CO) 5 , 2 it yields the coordinatively unsaturated intermediate, Fe(CO) 4 , which has the triplet ground state. This result has been veried both experimentally [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][48][49][50][51][52][53] and theoretically. [54][55][56][57][58][59][60][61] However, both Ru(CO) 4 and Os(CO) 4 are predicted to have a singlet ground state.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The available experimental observations show that upon COphotolysis of the pentacarbonyl metal complex M(CO) 5 , 2 it yields the coordinatively unsaturated intermediate, Fe(CO) 4 , which has the triplet ground state. This result has been veried both experimentally [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][48][49][50][51][52][53] and theoretically. [54][55][56][57][58][59][60][61] However, both Ru(CO) 4 and Os(CO) 4 are predicted to have a singlet ground state.…”
Section: Introductionmentioning
confidence: 69%
“…This theoretical observation is in good agreement with many experimental results. 2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][33][34][35][36][37] For the Ru(CO) 5 and Os(CO) 5 model compounds, both ruthenium and osmium pentacarbonyls have similar photochemical and thermal potential energy proles. The computations also show that both Ru(CO) 4 and Os(CO) 4 fragments feature a singlet electronic ground state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods rely on ultraviolet (UV) laser photolysis followed by detection methods based on UV absorption (20), chemical trapping (21,22), IR absorption (23,24,25) and ionization (5,6,26,27).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In fact, single and multiphoton dissociation of transition metal carbonyls in the gas and liquid phase have been extensively studied by various spectroscopic methods [129][130][131][132][133][134][135][136][137][138][139][140][141][142][143] including transient light absorption spectroscopy. 143-150 It was found that in the gas phase several carbonyls could be lost upon photolysis of the complex with UVlight.…”
Section: 2mentioning
confidence: 99%